2009
DOI: 10.1111/j.1365-294x.2009.04386.x
|View full text |Cite
|
Sign up to set email alerts
|

Female‐biased dispersal under conditions of low male mating competition in a polygynous mammal

Abstract: Sex-biased dispersal is a common phenomenon in birds and mammals. Competition for mates has been argued to be an important selective pressure favouring dispersal. Sexual differences in the level of intrasexual competition may produce asymmetries in the costs-benefits balance of dispersal and philopatry for males and females, which may favour male-biased dispersal in polygynous species such as most mammals. This being the case, condition-dependent dispersal predicts that male-bias should decrease if mating comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 101 publications
1
48
0
1
Order By: Relevance
“…Here, we have shown that the correlation of population and gene flow increase should not be assumed, even in species with long-distance dispersal capabilities, such as the brown bear. Several studies have found that dispersal decisions are condition dependent and consequently dispersal rate and frequency may vary among locations and individuals [8893]. However, as gene flow is widely accepted to be an important factor in population viability [1] and to ensure the long-term existence of the Scandinavian brown bear population, future studies should try to detangle natural, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have shown that the correlation of population and gene flow increase should not be assumed, even in species with long-distance dispersal capabilities, such as the brown bear. Several studies have found that dispersal decisions are condition dependent and consequently dispersal rate and frequency may vary among locations and individuals [8893]. However, as gene flow is widely accepted to be an important factor in population viability [1] and to ensure the long-term existence of the Scandinavian brown bear population, future studies should try to detangle natural, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, cases of female-biased dispersal have also been described in mammalian species, such as the greater sac-winged bat (Nagy et al 2007) and porcupines (Sweitzer and Berger 1998). For some species, such as the red deer, both male- (Catchpole et al 2004) and female-biased (Pérez-González and Carranza 2009) dispersal have been suggested. In cetaceans, male-biased dispersal has been inferred only in species that inhabit environments where prey resources are predictable (Möller 2012), whilst species living in unpredictable environments have symmetrical sex dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…We have not found evidence on the influence of sex ratio on the number of bison moving out of the forest; however, until the late 1980s, the sex ratio of bison calves was male biased (Hayward et al 2011). This indicates stronger mate competition between males that might force their dispersal (Handley and Perrin 2007; Pérez-González and Carranza 2009). In the closely related American wood bison ( B .…”
Section: Discussionmentioning
confidence: 99%